2019
DOI: 10.1175/jas-d-18-0234.1
|View full text |Cite
|
Sign up to set email alerts
|

Updraft Constraints on Entrainment: Insights from Amazonian Deep Convection

Abstract: Mixing of environmental air into clouds, or entrainment, has been identified as a major contributor to erroneous climate predictions made by modern comprehensive climate and numerical weather prediction models. Despite receiving extensive attention, the ad hoc treatment of this convective-scale process in global models remains poor. On the other hand, while limited-area high-resolution nonhydrostatic models can directly resolve entrainment, their sensitivity to model resolution, especially with the lack of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Finally, we comment on the negative correlation between « and w (or similarly, the positive correlation between « and w 21 , not shown, which has a correlation coefficient of 0.243 from the theoretical model). Similar relationships have also been found in previous modeling (e.g., Neggers et al 2002;Lu et al 2016;Zhang et al 2016;Anber et al 2019) and observational (Lu et al 2016) studies, with generally larger correlations than found here. A complicating factor in interpreting such relationships is that while w might be expected to influence «, « also directly drives changes in w through momentum mixing and especially buoyancy dilution.…”
Section: Discussion and Implications For Fractional Entrainment Ratessupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we comment on the negative correlation between « and w (or similarly, the positive correlation between « and w 21 , not shown, which has a correlation coefficient of 0.243 from the theoretical model). Similar relationships have also been found in previous modeling (e.g., Neggers et al 2002;Lu et al 2016;Zhang et al 2016;Anber et al 2019) and observational (Lu et al 2016) studies, with generally larger correlations than found here. A complicating factor in interpreting such relationships is that while w might be expected to influence «, « also directly drives changes in w through momentum mixing and especially buoyancy dilution.…”
Section: Discussion and Implications For Fractional Entrainment Ratessupporting
confidence: 92%
“…11, but for the moist environment with R H 5 0.85. in driving variability in « (this can be parsed in our model, which is one of the main benefits of a highly simplified framework). Larger w decreases the time for mixing to occur for rising parcels in our model, which has been invoked to explain an inverse relationship between « and w (e.g., Neggers et al 2002;Anber et al 2019); however, this effect is compensated by increased horizontal shear and larger mixing coefficients when w is larger.…”
Section: Discussion and Implications For Fractional Entrainment Ratesmentioning
confidence: 64%
See 1 more Smart Citation
“…The treatment of the cloud entrainment/detrainment process has been identified as a bottleneck for current global climate model (GCM) representation of deep convection, as well as simulations to cloud‐resolving model (CRM) scales (e.g., Anber et al., 2019; Bretherton et al., 2004; Del Genio et al., 2012; Kain & Fritsch, 1990; Kim & Kang, 2012; Klocke et al., 2011; Romps, 2010; Stirling & Stratton, 2012). For instance, a small change to the parameterization of the entrainment rate can introduce a significant shift in the timing or amplitude of the convective diurnal cycle (e.g., Del Genio & Wu, 2010; Yang & Slingo, 2001), thereby altering the large‐scale circulation and resulting in significant climate variability (e.g., Hannah & Maloney, 2011; Maloney & Hartmann, 2001; Sanderson et al., 2008; Tokioka et al., 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past 2 decades has focused on refining the formulation of the entrainment rate, a key control on climate model sensitivity to greenhouse gas concentrations (Stainforth et al, 2005;Knight et al, 2007). Typically, this rate is represented by a constant parameter = θ or a parametric function = (z, ζ ; θ ) of height z and (usually local) plume and environmental properties encoded in the model state ζ (e.g., de Rooy et al, 2013;Yeo and Romps, 2013;Anber et al, 2019;Savre and Herzog, 2019;Cohen et al, 2020). Similarly, diffusive closures of various types have been commonly employed for boundary layer turbulence in the atmosphere and oceans.…”
Section: Process-based Parameterizationsmentioning
confidence: 99%